Depressing liquid phase separation and macrosegeregation of Fe–Sn immiscible alloys by Cu alloying. (February 2014) - Lu, W. Q.; Zhang, S. G.; Li, J. G.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of Cu addition on the liquid phase separation and macrosegregation of Fe0·42Sn0·58 immiscible alloy was investigated based on thermal analysis, microstructural observations, thermodynamic and dynamic calculations. By increasing the Cu content, a structure with drastically diminished or even free of macrosegregation was realised. It revealed that Cu alloying has reduced the Gibbs free energy of mixing and temperature dependent coefficient of interfacial tension of liquids, thus depressing not only the frequency of collision and coagulation of the minor phase globules but also the liquid phase separation. As a viable and convenient means, alloying shows promise in obtaining homogeneous structure of immiscible materials.